Pembuatan Larvitrap Berbasis Limbah Plastik Dalam Menurunkan Kepadatan Nyamuk Vektor DBD Di Desa Tanjung Baru, Kecamatan Jati Agung, Kabupaten Lampung Selatan - Emantis Rosa; Yulianti; Selvi Marcelia; Linda Septiani (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Larvitrap is a mosquito trap intended for control at the pre-adult stage of vector mosquitoes in an effort to reduce mosquito density in nature. In the development of mosquitoes, the pre-adult stage is an important stage because the critical point in the mosquito life cycle is at the pre-adult stage, namely the egg and larval stages. The term larvitrap, its uses and benefits are not widely known and understood by the community in Tanjung Baru Village, Jati Agung District. Therefore, this counseling was carried out which was aimed at mothers and young women on how to make it. The results of the community service activities showed that there was a change in knowledge and understanding about making larvitraps which from the analysis results showed an increase in knowledge from participants from a low percentage to a high percentage (35% - 65%) with an average increase of 30%.